Constraints Faced by Dairy Farm Women in Improved Animal Husbandry Practices of Banaskantha District of North Gujarat - Patel, Khusvant; Chaudhary, G. M.; Ghasura, R. S.; Aswar, B. K. (Indian Journal of Hill Farming, 2016)
The present study was undertaken in six talukas of Banaskantha district of North Gujarat area. From each taluka, two villages were included at random, thus making a total of 12 villages for survey. Ten respondents from each village were selected at random making a list of total 120 respondents for this study. The ex-post facto design was followed .The most important constraints faced by dairy farm women in economical constraints, technical constraints, input-supply constraints and administrative constraints.